INVESTMENT QUESTIONS WHICH INVOLVE THE METHOD OF DISTRIBUTING PARTNERSHIP PROFITS. - Watson, Robert H. (The Accounting Review, 1952)
Abstract There are two types of investment questions, which involve the method used in distributing partnership profits. These are: (1) The computation of the profit before allowances, which make two methods of profit distribution of equal effect. When this profit figure is determined, it can easily be seen that one method is preferable if profits exceed the figure, while the other method is preferable if profits are less than that figure; and (2) The computation of the effect of an additional investment in the partnership under given conditions. Such a figure can then be compared with the return possible under alternative investment opportunities. When one of the alternatives involves tax-exempt securities, the return after taxes is the more significant figure. Each of the above situations is illustrated in this article by a correspondingly numbered example. One case analyzes options before a partner who is given the option of an increase in percentage of profit/loss, but a decrease in fixed salary. Another case presents investment options before a partner with variable rate of interest.